Dampak Pemasyarakatan Buku Kesehatan Ibu dan Anak Terhadap Perilaku Kesehatan Komunitas Saran - Adi, Isbandi Rukminto (Jurnal Ilmu Kesejahteraan Sosial, 2006)
The Health condition has been recognized as one of the indicators of the welfare condition in one community. In relation to that assumption, this article will describe the condition of mother and children in such areas in Indonesia which related to the Official Development Assisstance (ODA) programme which had been introduced by the Japan International Cooperation Agency. The Maternal and Child Health (MCH) handbook programme had been undertaken for about 10 years and has shown different results in many different areas in Indonesia. This article will show the effect of the MCH handbook programme to the mother’s child health behaviour in one village in Indonesia. The village was chosen because of their involvement in the MCH handbook programme for about the last 9 years.